A 50-Year-Old Male Patient with Toxic Epidermal Necrolysis (TEN) and Diabetes Mellitus Type 2: A Case Report - Patresya Lantan (HM Publisher, 2023)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, life-threatening conditions with high morbidity and mortality characterized by necrosis and extensive shedding of the epidermis in the vesiculobullous skin, orifice mucosa, and eyes as well, accompanied by severe general symptoms in the patient. SJS/TEN supportive care management varies widely. The difference is in the severity found based on the area of the affected skin surface. The most common cause is a hypersensitivity reaction to a drug. A 50-year-old man went to the emergency room (ER) with complaints of developing blisters, a rash accompanied by extensive peeling of the skin on the face, eyes, lips, chest, back, and genitals. 2 days before the onset of the complaint, the patient had a history of taking medication suggested by a nurse tetracycline and paracetamol. On physical examination, while in the emergency room, epidermolysis in the patient's body was found to be around 40% marked with a positive Nikolsky sign, and the SCORTEN found in this patient was 4. The management of this patient was in the form of keeping the patient's airway clear, administering adequate intravenous fluids, high doses of intravenous steroids, wound care, close patient observation, and care from other multidisciplinary disciplines such as internal medicine, anesthesia, ophthalmology, and surgery.